2013
DOI: 10.1002/adfm.201300287
|View full text |Cite
|
Sign up to set email alerts
|

Thieno[3,2‐b]thiophene‐diketopyrrolopyrrole Containing Polymers for Inverted Solar Cells Devices with High Short Circuit Currents

Abstract: The synthesis and characterization four diketopyrrolopyrrole containing conjugated polymers for use in organic photovoltaics is presented. Excellent energy level control is demonstrated through heteroatomic substitution whilst maintaining similar solid state properties as shown by X-ray diffraction and atomic force microscopy. Inverted solar cells were fabricated with the best devices having short circuit currents exceeding 16 mA cm − 2 and effi ciencies of over 5% irrespective of whether [6,6]-phenyl-C 61 -bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 51 publications
4
71
0
Order By: Relevance
“…S10 shows the XRD patterns of the blend films in the out-of-and in-plane directions. As expected, the intensities of the diffraction peaks gradually increased and peak narrowing occurred upon increasing the annealing temperature in both the out-of-and in-plane XRD profiles, indicating that the degree of crystallinity greatly increased [33]. In particular, in the in-plane XRD diffractogram, a distinct diffraction signal at 2θ=2.6170.021 became more enhanced as the annealing temperature increased, which is associated with increased P(NDI2OD-T2) crystallites ( Figure S11) having edge-on morphology.…”
supporting
confidence: 73%
“…S10 shows the XRD patterns of the blend films in the out-of-and in-plane directions. As expected, the intensities of the diffraction peaks gradually increased and peak narrowing occurred upon increasing the annealing temperature in both the out-of-and in-plane XRD profiles, indicating that the degree of crystallinity greatly increased [33]. In particular, in the in-plane XRD diffractogram, a distinct diffraction signal at 2θ=2.6170.021 became more enhanced as the annealing temperature increased, which is associated with increased P(NDI2OD-T2) crystallites ( Figure S11) having edge-on morphology.…”
supporting
confidence: 73%
“…In contrast to other donor-acceptor copolymers the low energy absorption band is much stronger and broader than the high energy one, which is a preliminary indication that the traditional model describing a 'camel-back' absorption spectrum does not apply directly to these materials. 16 The absorption spectra of these three materials in solution show more clearly resolved structure ( Figure 2b) with two contributions within the broad low energy absorption band. The absorption spectra are normalised in order to compare their shapes.…”
Section: Absorption Spectroscopymentioning
confidence: 96%
“…[1][2][3][4][5][6] Particularly for photovoltaic applications, the low energy gaps of donor-acceptor copolymers are attractive since they can be tuned to optimise harvesting of the solar emission spectrum. 5,10,[14][15][16][17] The high photovoltaic performance of D-A copolymers has been attributed in part to effective charge carrier transport, [18][19][20] but particularly to efficient charge photogeneration related to the charge transfer character of the longest-wavelength electronic transitions. 1,[9][10][11][12][13] One particularly interesting electron-accepting unit is diketopyrrolopyrrole (DPP), which is highly electron-deficient and so can provide very low energy gap materials when combined with an electron rich donor unit such as thiophene or its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…To tune the coplanarity of PDPP3T, Janssen et al [97] introduced methyl into the thiophene group of DPP unit, and a higher performance ultra-LBG polymer PDPP3MT was achieved with PCE of 6.8 % in the classic device configuration. Bronstein et al [98,99] reported the synthesis and polymerization of a novel thieno[3,2-b]thiophene-DPP-based building block in recent years. Copolymerization with thiophene afforded the resulting polymer, PTT-DPP-T, with a high hole mobility of 1.95 cm 2 V −1 s −1 .…”
Section: Diketopyrrolopyrrole (Dpp)-based Polymersmentioning
confidence: 99%